Emerging structural models for governance of public hospitals. Issue 2 (22nd May 2019) - Lipunga, Andrew Munthopa; Tchereni, Betchani M.H.; Bakuwa, Rhoda Cythia
Abstract : Purpose: The purpose of this paper is to present the contemporary understanding and emerging structural models of organisational governance of public hospitals in order to provide evidence-based guidance to countries that are reforming their public hospital governance structures in line with best practice. Design/methodology/approach: The paper uses the structural dimension of Cooper, Fusarelli and Randall's policy model and institutional theory to review the legislative frameworks of four model countries supported by extant literature. Findings: The paper conceptually distinguishes health system governance and organisational governance in the health system. It further visualises the emerging alternative legislative models of organisational governance and a hierarchy of governors applicable to public hospitals. Originality/value: The paper provides critical knowledge for understanding organisational governance within health system governance framework and develops tools that can be used in reforming institutional mechanism of organisational governance of public hospitals.